Cohesive Devices on Abstracts of Sinta-5 Accredited in English Journal: A Discourse Analysis Study - Muhammad Saibani Wiyanto; Annisa Brilianty; Suparti Suparti; Fitri Resti Wahyuniarti; Adib Darmawan (Universitas Muhammadiyah Malang, 2025)
In academic writing, cohesion is vital in ensuring clarity and facilitating reader comprehension, particularly in concise research abstracts that summarize key findings. This research aims to identify the types of cohesive devices and explain the use of cohesive devices in abstracts. The object of the research was 21 abstract journals. Data were collected through documentation and analyzed using qualitative content analysis as proposed by Mayring (2014). The analysis involved categorization, abstraction, and coding of the text. The results showed that there were 1113 exemplary of cohesive devices. In addition to that, collocation was the most frequently used device, appearing in 430 instances, then reiteration in 269 instances, references in 291 instances, suggesting a firm reliance on these for coherence. Conjunctions were also extensively used, with 117 instances, while ellipsis appeared only four instances as nominal ellipsis. The substitution was noted just twice, including both nominal and verbal forms. The research concludes that collocations and reiteration significantly enhance the clarity and flow of academic writing, with conjunctions aiding logical progression. The limited role of substitution and ellipsis highlights their specific, less frequent applications in maintaining textual cohesion and coherence. This analysis underscores the importance of various cohesive devices in effectively conveying research findings and ensuring reader comprehension of academic abstracts.